2D real space visualization of d values in polycrystalline bulk materials of different hardness. Issue 2 (31st March 2021) - Mizusawa, Mari; Sakurai, Kenji
Abstract : A new imaging method to visualize differences of d values in the same sample has been applied to bulk steel materials. Some crystal grains are visible, and the strains caused by the Vickers mark are also quantitatively visualized. Abstract : Conventional X‐ray diffraction measurements provide some average structural information, mainly on the crystal structure of the whole area of the given specimen, which might not be very uniform and may include different crystal structures, such as co‐existing crystal phases and/or lattice distortion. The way in which the lattice plane changes due to strain also might depend on the position in the sample, and the average information might have some limits. Therefore, it is important to analyse the sample with good lateral spatial resolution in real space. Although various techniques for diffraction topography have been developed for single crystals, it has not always been easy to image polycrystalline materials. Since the late 1990s, imaging technology for fluorescent X‐rays and X‐ray absorption fine structure has been developed via a method that does not scan either a sample or an X‐ray beam. X‐ray diffraction imaging can be performed when this technique is applied to a synchrotron radiation beamline with a variable wavelength. The present paper reports the application of X‐ray diffraction imaging to bulk steel materials with varying hardness. In this study, the distribution of lattice distortion of hardness test blocks with different hardness was examined. Via this 2D visualization method, the grains of the crystals with low hardness are large enough to be observed by X‐ray diffraction contrast in real space. The change of the d value in the vicinity of the Vickers mark has also been quantitatively evaluated.